Phylogeny and divergence of the 100 most common Salmonella serovars available in the NCBI Pathogen Detection database - Yang, Linghuan; Samut, Hilal; Kemmerling, Leonie; Orsi, Renato Hohl; Wiedmann, Martin; Chen, Ruixi; Resendiz-Moctezuma, Cristina (Frontiers in Microbiology, 2025)
Despite the emergence of whole genome sequencing (WGS) for Salmonella characterization, serotype assignment remains important as it allows identification of Salmonella subgroups that differ in distribution, virulence, and ecology. However, it has been shown that multiple divergent lineages of the same Salmonella serovar may have evolved independently multiple times and may present distinct epidemiological characteristics. Previous studies that aimed to identify the phylogeny of certain Salmonella serovars often used isolates from specific geographical locations or outbreaks and a small number of isolates to infer the phylogeny. To address these limitations and to advance the understanding of Salmonella’s evolutionary patterns, we (i) identified the phylogenetic grouping (i.e., mono-, para-, or polyphyly) of the 100 most common Salmonella serovars analyzing 63,204 genomes available in the NCBI Pathogen Detection database, (ii) identified, for each polyphyletic serovar, the lineages that contain the majority of genomes, and (iii) inferred the antigen divergence between the five most common serovars (i.e., Salmonella Enteritidis, Typhimurium, Newport, I 4,[5],12:i:-, and Infantis) and their respective closely-related serovars. Among the 100 most common Salmonella serovars analyzed, 19 serovars are monophyletic, nine are paraphyletic, and 72 are polyphyletic. In 47 of the 72 polyphyletic serovars, one lineage contains more than 90% of the serovar’s confirmed genomes. Antigen divergence results suggest that serovars Typhimurium and I 4,[5],12:i:- (often referred to as monophasic Typhimurium) have emerged independently of each other multiple times, except for the major I 4,[5],12:i:- lineage, which emerged from the major Typhimurium lineage. Furthermore, divergence in Salmonella serovars appears to primarily occur through modifications in the H1 antigen. Hence, this study shows that (i) a much larger number of serovars than previously known are polyphyletic; (ii) serovars previously known to be polyphyletic contain more lineages than previously known; and (iii) many serovars include lineages that only have a few isolates with a given serovar. Our data suggests that, in the age of genomics, molecular serotyping should be combined with other phylogenetically informative approaches to not just assign a serovar but to also indicate the serovar lineage for polyphyletic and paraphyletic serovars.